Chronic Viral Hepatitis in a Cohort of Inflammatory Bowel Disease Patients from Southern Italy: A Case-Control Study - Losurdo, Giuseppe (Pathogens, 2020)
We performed an epidemiologic study to assess the prevalence of chronic viral hepatitis in inflammatory bowel disease (IBD) and to detect their possible relationships. Methods: It was a single centre cohort cross-sectional study, during October 2016 and October 2017. Consecutive IBD adult patients and a control group of non-IBD subjects were recruited. All patients underwent laboratory investigations to detect chronic hepatitis B (HBV) and C (HCV) infection. Parameters of liver function, elastography and IBD features were collected. Univariate analysis was performed by Student’s t or chi-square test. Multivariate analysis was performed by binomial logistic regression and odds ratios (ORs) were calculated. We enrolled 807 IBD patients and 189 controls. Thirty-five (4.3%) had chronic viral hepatitis: 28 HCV (3.4%, versus 5.3% in controls, p = 0.24) and 7 HBV (0.9% versus 0.5% in controls, p = 0.64). More men were observed in the IBD–hepatitis group (71.2% versus 58.2%, p < 0.001). Patients with IBD and chronic viral hepatitis had a higher mean age and showed a higher frequency of diabetes, hypertension and wider waist circumference. They suffered more frequently from ulcerative colitis. Liver stiffness was greater in subjects with IBD and chronic viral hepatitis (7.0 ± 4.4 versus 5.0 ± 1.2 KPa; p < 0.001). At multivariate analysis, only old age directly correlated with viral hepatitis risk (OR = 1.05, 95%CI 1.02–1.08, p < 0.001). In conclusion, the prevalence of HBV/HCV in IBD is low in our region. Age may be the only independent factor of viral hepatitis–IBD association. Finally, this study firstly measured liver stiffness in a large scale, showing higher values in subjects with both diseases.